Effects of linear heat input on microstructure and corrosion behavior of an austenitic stainless steel processed by wire arc additive manufacturing. (March 2020) - Wen, DongXu; Long, Ping; Li, JianJun; Huang, Liang; Zheng, ZhiZhen
Abstract: The effects of linear heat input (LHI) on the microstructure and corrosion behavior of an austenitic stainless steel processed by wire arc additive manufacturing (WAAM) are studied. It is found that the primary dendrites spacing of the studied steel increases from 18 μm to 23 μm, when the LHI increases from 219 J ⋅ mm - 1 to 590 J ⋅ mm - 1 . But the δ-ferrite contents under high and low LHIs are similar. Moreover, the passivation voltage range decreases and the corrosion current density increases with the increase of LHI. The poor corrosion resistance for the studied steel under high LHI is highly related with the segregation of Cr and Mo atoms in the Ni-poor δ-ferrite. Highlights: The effect of linear heat input on a stainless steel processed by WAAM is studied. The primary dendrites grow quickly during the WAAM under high linear heat input. The poor corrosion property is related with the segregation of Cr/Mo in δ-ferrite.